Regulatory Effect of Sishen Pill on Tfh Cells in Mice With Experimental Colitis - Liu, Xue-Ke; Zhao, Hai-Mei; Wang, Hai-Yan; Ge, Wei; Zhong, You-Bao; Long, Jian; Liu, Duan-Yong (Frontiers in Physiology, 2020)
The T follicular helper T (Tfh) cells play a significant role in the pathogenesis of inflammatory bowel disease (IBD) , which is regulated by the Bcl-6/Blimp-1 pathway. Some studies have suggested that regulating activation of the Bcl-6/Blimp-1 pathway should be an effective method to treat IBD. Sishen Pill (SSP) has frequently been used to treat chronic colitis. Its mechanism is related to the downstream proteins in the Bcl-6/Blimp-1 pathway. However, it is unknown whether SSP regulates the function and differentiation of Tfh cells to treat IBD. In the present study, chronic colitis was induced by dextran sodium sulfate and treated with SSP for 7 days. SSP effectively treated chronic colitis, and regulated the balance between Tfh10, Tfh17 and T follicular regulatory cells, and inhibited expression of Bcl-6, inducible T-cell costimulator, programmed death (PD)-1 and PD-ligand 1 on the surface of Tfh cells, and increased the level of Blimp-1. SSP inhibited activation of BcL-6, phosphorylated signal transducer and activator of transcription (p-STAT)3, signal lymphocyte activation molecule (SLAM)-associated protein but improved Blimp-1 and STAT3 expression in colonic tissues. The results indicated that SSP regulated the differentiation and function of Tfh cells to treat chronic ulcerative colitis via the Bcl-6/Blimp-1 pathway.